Representation of Poverty as A Social Reality in the Novel Teruslah Bodoh Jangan Pintar By Tere Liye: Swingewood Theory - Sindi Eka Yunita; Moh Ahsan Shohifur Rizal (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
later